The Effects of Nutritious Food on Stunting - Desi Kartika Sari; Sunanto; Iis Hanifah (Health and Technology Journal (HTechJ), 2023)
Stunting is a problem of chronic malnutrition for a long time which interferes with children's growth so that children are shorter than their legal age. This study aims to analyze the effect of nutritious food on stunting in Sukodadi Village, the working area of ​​the Paiton Health Center, Paiton District, Probolinggo Regency. This study used an experimental design with a total sampling technique form of all 30 stunted toddlers in Sukodadi Village. Research instruments in the form of questionnaires and anthropometry. The data is processed by editing, coding, and tabulating techniques. The results showed that additional food in the form of quail eggs had been distributed to all respondents. However, only 26 respondents (87%) have consumed it regularly and correctly. The other four respondents failed to consume properly and continued to experience stunting. So, there is an effect of nutritious food on stunting in Sukodadi Village, with a p-value: of 0.001. The author suggests that the results of this study can be applied in other areas by providing additional food in the form of quail eggs to prevent stunting.